Allantoin induces pruritus by activating MrgprD in chronic kidney disease. Issue 4 (6th March 2023) - Yang, Yan; Sun, Yulin; Zhu, Chan; Shen, Xinyu; Sun, Jianmei; Jing, Tao; Jun, Shi; Wang, Changming; Yu, Guang; Dong, Xinzhong; Sheng, Meixiao; Tang, Zongxiang
Abstract: Chronic kidney disease (CKD) is a disease with decreased, irreversible renal function. Pruritus is the most common skin symptom in patients with CKD, especially in end‐stage renal disease. The underlying molecular and neural mechanism of CKD‐associated pruritus (CKD‐aP) remains obscure. Our data show that the level of allantoin increases in the serum of CKD‐aP and CKD model mice. Allantoin could induce scratching behavior in mice and active DRG neurons. The calcium influx and action potential reduced significantly in DRG neurons of MrgprD KO or TRPV1 KO mice. U73122, an antagonist of phospholipase C, could also block calcium influx in DRG neurons induced by allantoin. Thus, our results concluded that allantoin plays an important role in CKD‐aP, mediated by MrgprD and TrpV1, in CKD patients.